Integrating Local Culture into Parental Nutrition Education: Evidence from an Ethnoparenting Based Intervention in West Java - Padwika, Dian Ramadhani; Rudiyanto; Yeni Rachmawati; Agustin, Mubiar; Mwariko, Sadick Akida (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
The consumption of unhealthy snacks among young children is increasing, while parents’ knowledge of children’s nutritional needs remains limited. This study aimed to evaluate the impact of ethnoparenting-based training on improving parents’ knowledge of early childhood nutrition in Karangsari Village, West Java. The focus of the training was to develop an innovative nutritious snack, Manca, made from local ingredients, namely Manyung fish bone meal and Leunca vegetables, both rich in calcium and phosphorus. This research employed a pre-experimental design with pre-test and post-test procedures. The sample consisted of 30 parents of children aged 2 to 6 years, selected through purposive sampling. Data were analyzed using the Shapiro-Wilk test, Levene test, and paired t-test. The results indicated a significant improvement in parents’ knowledge, with the mean post-test score increasing by 37 points from 48 to 85. The findings align with Bandura’s Social Learning Theory and Bronfenbrenner’s Ecological Systems Theory, emphasizing the role of parental modeling and cultural context in shaping nutritional practices. The ethnoparenting-based training proved effective in enhancing parents’ awareness of balanced nutrition for young children. This study highlights the importance of culturally grounded approaches in health and education programs for parents. The findings imply the need to integrate ethnoparenting-based training into early childhood care and education (ECCE) policies globally, particularly in multicultural contexts where parental knowledge of nutrition varies widely. By promoting culturally sensitive nutrition behaviors among parents, this study contributes to the global discourse on improving child health outcomes amid rising cases of undernutrition and overnutrition. Furthermore, incorporating local practices into educational interventions may serve as a model for sustainable and culturally responsive public health initiatives worldwide.